Getting to the Root of Organic Inputs in Groundwaters: Stygofaunal Plant Consumption in a Calcrete Aquifer - Saccò, Mattia; Campbell, Matthew A.; Nevill, Paul; Humphreys, William F.; Blyth, Alison J.; Grierson, Pauline F.; White, Nicole E. (Frontiers in Ecology and Evolution, 2022)
Groundwater environments interact with and support subterranean biota as well as superficial aquatic and terrestrial ecosystems. However, knowledge of subterranean energy flows remains incomplete. Cross-boundary investigations are needed to better understand the trophic structures of groundwater ecosystems and their reliance on carbon inputs from aboveground. In this study we used carbon and nitrogen stable isotope analyses combined with radiocarbon fingerprints to characterise organic flows in groundwater ecosystems. We coupled these data with DNA metabarcoding of the gut contents of stygofauna to further elucidate organic matter sources and shifts in diet preferences. Samples were collected from the arid zone Sturt Meadows calcrete aquifer under low rainfall (LR) and high rainfall (HR) conditions. Bayesian modelling of Δ14C, δ13C and δ15N data indicated that primary consumers (copepods) incorporated mainly particulate organic carbon (POC) under LR but during HR shifted to root derived material (either exudates or direct root grazing). By contrast, diets of secondary consumers (amphipods) were dominated by root material under both LR and HR. Our DNA metabarcoding-based results indicate that amphipods relied primarily on root inputs from perennial trees (likely Eucalyptus and Callitris) during the dry season (LR). Under HR, diets of both amphipods and copepods also included organic material derived from a broad range of more shallow rooted shrubs, and ephemeral herbs and grasses. Our findings illustrate the complexity of functional linkages between groundwater biota and surface terrestrial ecosystems in environments where aboveground productivity, diversity and organic matter flux to groundwater are intimately linked to often episodic rainfall.